2001
DOI: 10.1093/emboj/20.24.7060
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine receptors are required for agrin-induced clustering of postsynaptic proteins

Abstract: We have investigated the role of acetylcholine receptors (AChRs) in an early step of postsynaptic assembly at the neuromuscular synapse, the clustering of postsynaptic proteins induced by nerve-released agrin. To achieve this, we used two variants of C2 myotubes virtually lacking AChRs and C2 cells in which surface AChRs were down-regulated by AChR antibodies. In all cases, agrin caused normal clustering of the agrin receptor component MuSK, a-dystrobrevin and utrophin, but failed to aggregate AChRs, a-and b-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 43 publications
4
59
0
Order By: Relevance
“…However, this hypothesis was brought into question by experiments in C2 myotubes showing that rapsyn does not form a network in the absence of acetylcholine receptors (8,9). Our results are consistent with the latter observations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, this hypothesis was brought into question by experiments in C2 myotubes showing that rapsyn does not form a network in the absence of acetylcholine receptors (8,9). Our results are consistent with the latter observations.…”
Section: Discussionsupporting
confidence: 89%
“…Recombinant rapsyn expressed in heterologous systems spontaneously aggregates underneath the plasma membrane (3), suggesting that rapsyn might first form a wide scaffold to which receptors can subsequently dock (6). On the other hand, rapsyn and the receptor are cotransported in membrane vesicles toward the plasma membrane, and the receptor is necessary for rapsyn clustering in C2 myotubes, raising the possibility that rapsyn only forms short bridges linking receptors together to form a large cluster (7)(8)(9). Furthermore, the number of rapsyn-binding sites per receptor (a heteropentamer) has been variously estimated to be between one and five (6,10,11).…”
mentioning
confidence: 99%
“…GABA A -mediated synaptic transmission is crucial for maintaining correctly matched symmetric synapses and avoiding the formation of heterologous synapses. The fact that GABA A receptors are dispensable for initial synapse formation finds a clear parallel at the neuromuscular junction, where the postsynaptic apparatus can initially develop in myotubes devoid of acetylcholine receptors, although the receptors are needed for the full differentiation of the synaptic junction (Marangi et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…When rapsyn was expressed in fibroblasts (Phillips et al, 1991) or in Xenopus oocytes (Froehner et al, 1990), rapsyn formed selfclusters without the coexpression of AChRs. On the other hand, in C2 myotubes lacking expression of AChRs, the stability of rapsyn was decreased and agrin treatment failed to cause aggregation of rapsyn (Marangi et al, 2001). Our results from in vivo showed that rapsyn was capable of self-clustering in the absence of receptor.…”
Section: Discussionmentioning
confidence: 99%